Cultural experiences, challenges and coping strategies of Somali refugees in Malaysia: implications for cross-cultural counseling in a plural society - Ssekamanya, Siraje Abdallah; Noor , Mohamed Abdinoor (2012)
Using the qualitative approach of phenomenology, this study explored the cultural adjustment experiences, challenges, and coping strategies of Somali refugees in Malaysia. Semi-structured interviews were used as the major strategy for data collection. Data were collected from 7 Somali refugees of various genders, ages, and educational backgrounds. Thematic analysis revealed six major areas of concern, that is, financial difficulties, communication barriers, inability to interact with the host community, technological difficulties, security concerns, and difficulties related to food and dress codes. Similarly, four coping skills have been found to be helpful, namely: gathering knowledge about the new culture, having previous cross-cultural experiences, financial support from family, an attitude of tolerance and patience. Support from friends and relatives and being optimistic played a major role. Implications of these findings for the development and organization of counseling services for Somali and other refugees in Malaysia are discussed.